Performance Enhancement of Mixed Matrix Membranes through the Incorporation of Alkanolamines for CO2/CH4 Separation - Rizwan Nasir; Hilmi Mukhtar; Zakaria Man; Maizatul Shima Bt. Shaharun; Mohamad Zailani Abu Bakar (Department of Chemical Engineering, Universitas Gadjah Mada, 2015)
Diethanolamine (DEA) solution was used in this study to enhance the performance of polyethersulfone (PES) – carbon molecular sieve (CMS) mixed matrix membrane (MMMs). These new amine mixed matrix membranes (A3Ms) were fabricated at room temperature by using fixed concentration of PES, CMS and different concentrations (5, 10 wt. %) of DEA. The developed mixed matrix membranes were characterized by using field emission scanning electron microscope (FESEM) and thermogravimetric analyser (TGA) in order to investigate the effect of DEA addition on morphology and thermal stability. Gas performance tests were also performed to measure the permeance and selectivity. The characterization results showed that the membranes were thermally stable, dense and non-porous. The gas performance tests showed that the permeance and selectivity of A3Ms is higher than the native PES membrane. CO2 permeance increases with the increase of DEA concentration. Hence it was found that with an addition of 10% (wt. %) DEA at a pressure of 2 bars, the CO2 permeance was increased from 50.86 to 127.06 GPU and the CO2/CH4 selectivity was also increased from 3.08 to 12.30.